The effect of religious background on the attitude towards sex selection - Anastasia A. Salame; Jospeh Nassif; Ghina S. Ghazeeri; Elie M. Moubarak; Antoine Hannoun; Antoine A. Abu Musa (Elsevier, 2019)
Objectives: Surveys of the general population regarding sex selection using pre-implantation genetic diagnosis are limited and were mainly conducted in the United States and Northern Europe. In those Western societies, surveys have shown that people's interest in using sex selection techniques is encouraged by the desire for a sexually balanced family. It is important to determine attitudes to sex selection in a wider range of countries especially that cultural differences exist among countries. Study design: A questionnaire-based cross-sectional study regarding attitudes towards sex selection for non-medical reasons was designed. One thousand five hundred participants of the reproductive age group presenting to the Women s Health Center at the American University of Beirut Medical Center were offered to complete the survey. The questionnaire included demographic details, obstetric and infertility history, opinions regarding sex selection, personal interest in expanding the family, and personal interest in choosing the sex of a future child. Results: The response rate was 86.6%. Nineteen per cent of the respondents considered it strictly prohibited, 38.8% considered the technique acceptable only if medically indicated while 33.4% believed that it should be available to all those who request it. Multivariate logistic regression on the predictors of the variable affecting the attitudes towards sex selection showed that the educational level, religious disapproval and the desire of the opposite sex of the already existing children were the only significant predictors. Conclusion: The middle-eastern multi-religious population studied has a negative attitude towards sex selection through pre-implantation genetic diagnosis. Religion, educational status and desire of children of both genders were identified as the significant predictors of the decision whether to accept sex selection or not. Keywords: Surveys and questionnaires, Sex preselection, Attitude, Humans